Morphological evidence of anabolic action of the drug histochrome in rats - O. S. Talalaeva; Ya. F. Zverev; V. M. Bryukhanov; Yu. G. Motin (Бюллетень сибирской медицины)
The aim of the investigation was to assess histochrome’s anabolic effect as a consequence of treatment of various doses in rats in conditions of prolonged physical training.Materials and methods. The experiments were performed on the Wistar’s rats. Experimental Group 1 was subcutaneously injected with histochrome in a dose of 1 mg/kg (n = 20) within 10 days, experimental group 2 was treated subcutaneously at a dose of 10 mg/kg (n = 20), and control group 3 received equivolume injections of isotonic sodium chloride (n = 20). Rat musclehypertrophy was induced using the method of forced swimming. A piece ofmuscle  was takenfor morphological examination a day after the first and last period of swimming. Hypertrophy of muscle fibers was evaluated by the cross-sectional diameter of muscle fibers, the average quantity of argyrophilic nucleolar organizer region (AgNOR) proteins and the percentage of nuclei with 1, 2, 3 or more AgNOR compared to intact (control) animals.Results. Microscopic morphological examination of M. gastrocnemius registered increase in diameter of muscle fiber by 19,4% (1 mg/kg) and by 60% (10 mg/kg). In the control group of rats an increase in a transverse section of muscle fibers was not found to be statistically significant.The study of biosynthetic nuclei activity of myosimplastus registered increase the AgNOR proteins in both examines groups of animals in comparison the less dynamics in control one. By 10th day of observation the quantity of myosimplastus with two AgNOR increased in a control group of rats by 10%. The maximum AgNOR proteins gained was marked in case of the prolonged use of histochrome in a dose 1 mg/kg.Conclusion. Histochrome enables the increase in dose-dependent biosynthetic processes in skeletal muscles of rats, providing the development of anabolic effect.